Flexural strengthening of RC continuous T beam using CFRP laminate: a review - Jumaat, Mohd Zamin; Rahman, M.M.; Alam, M.A. (Academic Journals, 2010)
Although a great deal of research has been carried out on simply supported reinforced concrete (RC) beams strengthened with Fibre-Reinforced Polymer composites (FRP), a few works has been focused on continuous beams. Particularly, experiments on strengthening the negative moment regions of continuous T beams are rare to find. This paper reviews 40 articles on CFRP strengthened RC beams and 6 articles on CFRP strengthened RC slabs. Existing 10 articles on CFRP strengthened RC continuous beams are critically reviewed. Finally, this paper attempts to address an important practical issue that is encountered in strengthening the negative moment region of RC continuous T beam. The negative moment region of continuous RC T beam is a critical region due to the concurrence of maximum moment and shear as well as installation restraint due to the presence of column. This paper also proposes a simple method of applying CFRP for strengthening the negative moment region of continuous T beam. Â© 2010 Academic Journals.